Design and first applications of the ITER integrated modelling & analysis suite. (30th October 2015) - Imbeaux, F.; Pinches, S.D.; Lister, J.B.; Buravand, Y.; Casper, T.; Duval, B.; Guillerminet, B.; Hosokawa, M.; Houlberg, W.; Huynh, P.; Kim, S.H.; Manduchi, G.; et al.
Abstract: The ITER Integrated Modelling & Analysis Suite (IMAS) will support both plasma operation and research activities on the ITER tokamak experiment. The IMAS will be accessible to all ITER members as a key tool for the scientific exploitation of ITER. The backbone of the IMAS infrastructure is a standardized, machine-generic data model that represents simulated and experimental data with identical structures. The other outcomes of the IMAS design and prototyping phase are a set of tools to access data and design integrated modelling workflows, as well as first plasma simulators workflows and components implemented with various degrees of modularity.